2018
DOI: 10.4066/biomedicalresearch.29-17-2913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hippophae rhamnoides extract on oxidative mucosal injury induced by cisplatin in rat jejunum

Abstract: Objectives: We aimed to assess the effect of Hippophae rhamnoides extract (HR) on oxidative stress induced by cisplatin (Cis) in rat small intestine tissue by evaluating the biochemical and gene expression levels and histopathological changes. Materials and methods: The control group and Cis group received distilled water, while the HR25+cisplatin (HR25+Cis) group and the HR50+cisplatin (HR50+Cis) group were given HR 25 and 50 mg/kg, respectively, orally for seven days. HR25+Cis, HR50+Cis, Cis groups were inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…It was demonstrated that HR extract reversed the biochemical changes induced by cisplatin such as the increase of malondialdehyde and proinflammatory cytokines, including IL-1β and TNF-α, as well as a decrease of oxidative parameters. It was concluded that extract of sea buckthorn fruit might exert a protective effect on the oxidative damage of intestinal tissue (Arslan et al, 2018). Furthermore, the beverages from the fruits of sea buckthorn were used to support the supplementation of Lactobacillus rhamnosus GG in the attenuation of LPS-induced colonic tissue damage in zebrafish (Sireswar et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…It was demonstrated that HR extract reversed the biochemical changes induced by cisplatin such as the increase of malondialdehyde and proinflammatory cytokines, including IL-1β and TNF-α, as well as a decrease of oxidative parameters. It was concluded that extract of sea buckthorn fruit might exert a protective effect on the oxidative damage of intestinal tissue (Arslan et al, 2018). Furthermore, the beverages from the fruits of sea buckthorn were used to support the supplementation of Lactobacillus rhamnosus GG in the attenuation of LPS-induced colonic tissue damage in zebrafish (Sireswar et al, 2020).…”
Section: Figurementioning
confidence: 99%